Effect of Loss Distribution on Deterrence Function of Tort Law - Negin Gholami; Mohammad Moloudi (پژوهشهای حقوقی)
In the tort liability, damages are distributed by modern institutions such as insurances, strict liability of companies or traditional and jurisprudential institutions such as kinsmanship. Although these loss distributive institutions have advantages such as assuring compensation of the injured or reducing the injurer’s burden of compensation, some analyzers believe that the facilities such institutions provide to the two parties can deteriorate the deterrence role of the civil liability and promote imprudence. Therefore although these institutions are in line with the tort liability system in terms of compensating the damage, they have a reverse effect in terms of deterrence and promote imprudence. In contrast, there are reasons that reject critique of the mechanism of these institutions. The reasons include the existence of other deterrent factors along with tort liability such as the sense of misrepresentation of individuals, the ineffectiveness attributable to the tort liability system in the realization of deterrence and the prediction of mechanisms in loss distributive institutions to prevent imprudence. Hence, the distributive institutions generally, unlike the initial perception, if don’t have a positive effect on deterrence, they don’t have at least negative effect on it and did not expedite the spread of it.